2012
DOI: 10.7314/apjcp.2012.13.8.4101
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Melatonine Against Radiation Induced Nephrotoxicity in Rats

Abstract: Protective Effect of Melatonine Against Radiation Induced Nephrotoxicity in Rats 13, 4101-4105 IntroductionKidneys are frequently included into the therapy area during radiotherapy applications. The extent of radiation damage depends on both dose and volume of radiation (Perez et al., 2008). Renal tolerance dose is 20 Gy in bilateral irradiation, while in unilateral exposure renal dysfunction starts in 15 Gy and renal function is completely lost in doses of 25-30 Gy. Concomitant use of cisplatin some chemicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
0
25
0
2
Order By: Relevance
“…Testis and kidneys are highly sensitive to radiation, and dose‐dependent toxicity occurs in this tissue (van Beek et al ., ; Perez & Halperin, ; Kucuktulu, ). It is well established that after radiation exposure, elevated levels of free radicals in mitochondria cause DNA, protein and lipid damage (Xiao & Whitnall, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Testis and kidneys are highly sensitive to radiation, and dose‐dependent toxicity occurs in this tissue (van Beek et al ., ; Perez & Halperin, ; Kucuktulu, ). It is well established that after radiation exposure, elevated levels of free radicals in mitochondria cause DNA, protein and lipid damage (Xiao & Whitnall, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously reported that administration of radiation to male patients with malignant diseases may cause temporary or permanent sterility by disruption of the normal cyclic process of spermatogenesis and impairment of fertility (Tarladacalisir et al ., ). Radiation nephropathy is one of the side effects of RT application, and it is even more important in patients with longer life expectancy, especially in children since clinical findings and the time elapsed in a wide spectrum (Kucuktulu, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro and in vivo studies have investigated the radioprotective effects of melatonin. Animal studies were conducted for various organs such as lung, heart, kidney, liver, gastrointestinal system, skin, testes, lenses, spinal cord and others [183][184][185][186][187][188][189][190][191]. Although the clinical applications for possible radioprotection of melatonin have suffered limitations, some have shown promising results.…”
Section: Melatoninmentioning
confidence: 99%
“…Melatonin is known to protect against oxidative injury of toxins and radiations with its free radical scavenging capacity (Kucuktulu, 2012). The current study showed low melatonin levels in CLL patients compared to their healthy controls.…”
Section: Discussionmentioning
confidence: 80%